Financial assets, debt and liquidity crises a Keynesian approach - Charpe, Matthieu; Chiarella, Carl; Flaschel, Peter; Semmler, Willi; Cambridge Books Online (Online service). (Cambridge New York Cambridge University Press, 2011)
"The macroeconomic development of most major industrial economies is characterized by boom-bust cycles. Normally such boom-bust cycles are driven by specific sectors of the economy. In the financial meltdown of the years 2007-2009 it was the credit sector and the real-estate sector that were the main driving forces. This book takes on the challenge of interpreting and modelling this meltdown. In doing so it revives the traditional Keynesian approach to the financial-real economy interaction and the business cycle, extending it in several important ways. In particular, it adopts the Keynesian view of a hierarchy of markets and introduces a detailed financial sector into the traditional Keynesian framework. The approach of the book goes beyond the currently dominant paradigm based on the representative agent, market clearing and rational economic agents. Instead, it proposes an economy populated with heterogeneous, rationally bounded agents attempting to cope with disequilibria in various markets"--Provided by publisher
Financial crises and the macroeconomy -- Part I. The Non-linear Dynamics of Credit and Debt Default: 2. Currency crises, credit crunches and large output loss; 3. Mortgage loans, debt default and the emergence of banking crises; 4. Debt deflation and the descent into economic depression -- Part II. Theoretical Foundations for Structural Macroeconometric Model Building: 5. Keynesian macroeconometric model building: a point of departure; 6. Intensive form and steady state calculations; 7. Partial feedback structures and stability issues -- Part III. Debt Crises: Firms, Banks and the Housing Markets: 8. Debt deflation: from low to high order macrosystems; 9. Bankruptcy of firms, debt default and banks the performance of banks; 10. Japan's institutional configuration and its financial crisis; 11. Housing investment cycles, workers' debt and debt default
Title from title screen (viewed on November 3, 2023)
Also issued in print format
Mode of access: World Wide Web
Keywords: Macroeconomics; Business cycles; Financial crises; Keynesian economics